Counseling psychology doctoral students' experiences of authenticity: a collaborative autoethnography. Issue 1 (2nd January 2023) - Yang, NaYeon; Jankauskaite, Greta; Gerstenblith, Judith A.; Hillman, Justin W.; Wang, Ruogu J.; Le, Thomas P.; Hill, Clara E.
ABSTRACT: Given the importance of authenticity in counseling psychology, we used a collaborative autoethnography approach to explore our experiences of authenticity as counseling psychology doctoral students. Six (3 women, 2 men, 1 gender flexible man; 3 European American, 2 Asian American, 1 Asian; 5 3 rd -year students, 1 2 nd -year student) students in one counseling psychology doctoral program in the Mid-Atlantic United States reflected on the factors that facilitated and hindered our ability to be authentic by writing four one-to-five page journal entries, reading the journals in four three-hour group meetings, receiving non-judgmental feedback, and editing the journal entries. In the journals, we explored our understanding of authenticity, the development of our authentic selves, our experience of authenticity in graduate school, the role of authenticity in our relationships, the way in which our authenticity has been shaped by external forces, and our process of balancing the costs and benefits when deciding whether or not to be authentic in a given situation. Themes that emerged from the data revealed that we had received mixed messages about authenticity in our graduate program and that our ability to be authentic varied depending on whether we were in the role of therapist, teacher, researcher, or student. Further, family and peer relationships, hierarchical structures, and privileged and marginalized social identities enhanced or inhibited our experiences of authenticity in graduate school. Implications for graduate students and recommendations for future research are discussed.